Education and work in the Argentinean pedagogical field - Vicente, María Eugenia (2018)
This article aims at contributing to the link between education and work in the Argentinean pedagogical field by means of a reconstruction of the structural modifications of the professional characteristics in the last forty years of Education Sciences Degree. The analysis suggests that the reconfiguration of the link between education and work in Education Sciences gives rise to other ways and conditions of knowledge production in the education field. These new characteristics have enabled progress on those conceptions that recognize Education Sciences as fragmented, hybrid and unstructured